(untitled) (Gestión y Gerencia, 2024)
The university, as a socially committed organization, produces internal and external impacts and has a commitment directly related to the institutional management philosophy. For this essay, opinions of authors were reviewed and reflections were prepared for the construction of knowledge by contrasting them with reality. Among the final musings, they highlight that the authorities of the alma mater must constitute themselves as proactive situational leaders committed to university social responsibility, willing to strengthen the knowledge transfer processes required in dissimilar sectors, starting from bioethics, through the synergistic integration of social actors, in order to offer responses to communities for sustainable human development.